REVITALISASI NILAI-NILAI HADIS DALAM DAKWAH DIGITAL: STUDI INTEGRATIF TENTANG TRAUMA RELIGIUS DAN PODCAST ISLAMI - Yenanda Putri Zanuba (Yayasan Baitul Hikmah al-Zain, 2025)
Religious trauma is a psychological problem that arises as a result of painful spiritual experiences, such as the misuse of religious teachings or excessive pressure from religious aspects. In this situation, digital preaching through podcast media can offer a more inclusive, profound, and calming alternative. This article explores how prophetic values found in hadith can be revived through Islamic podcasts as a response to religious trauma. This study applies a qualitative approach with content analysis of several episodes of the Escape podcast hosted by Ustadz Felix Siauw and Raymond Chin. The findings of the study show that the values in the hadith, such as rahmat (mercy), hikmah (wisdom), and tazkiyatun nafs (purification of the soul), are expressed in narratives that are free from judgment, encourage introspection, and strengthen spiritual connections. Thus, Islamic podcasts have the potential to become a digital means of preaching that is sensitive to situations of religious trauma, especially among young Muslims.